2021
DOI: 10.3390/tomography7040060
|View full text |Cite
|
Sign up to set email alerts
|

Development and Remodeling of Point-of-Care Ultrasound Education for Emergency Medicine Residents in Resource Limited Countries during the COVID-19 Pandemic

Abstract: The administration of an accurate and effective POCUS course is a crucial tool in improving health education and thus the health care system in low- to middle-income countries. The development of the ultrasound curriculum in these countries during the pandemic era is a major challenge for medical educators. Therefore, this study aims to survey the learner experience after implementing the POCUS curriculum for first-year emergency medicine residents. All learners responded to the survey. Our results demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(45 reference statements)
0
6
0
1
Order By: Relevance
“…(1) our residents had limited experience performing OB-GYN POCUS as they only used transabdominal ultrasonography in patients with abdominal pain and/or vaginal bleeding and a positive pregnancy test to screen for the presence of an intrauterine pregnancy (IUP) in the emergency department. It can also be noted that images collected from both transabdominal ultrasonography and transvaginal ultrasonography have ultrasound artifacts [19], which all emergency physicians who use the modality should have sufficient education and practice to be aware of these, and (2) from our previous study [14], it was noted that the frequency of this operation was less in number of times it was performed than other operations. Other results from this study showed that the competency of image acquisition for cardiac images demonstrated varied in score from 1-5.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(1) our residents had limited experience performing OB-GYN POCUS as they only used transabdominal ultrasonography in patients with abdominal pain and/or vaginal bleeding and a positive pregnancy test to screen for the presence of an intrauterine pregnancy (IUP) in the emergency department. It can also be noted that images collected from both transabdominal ultrasonography and transvaginal ultrasonography have ultrasound artifacts [19], which all emergency physicians who use the modality should have sufficient education and practice to be aware of these, and (2) from our previous study [14], it was noted that the frequency of this operation was less in number of times it was performed than other operations. Other results from this study showed that the competency of image acquisition for cardiac images demonstrated varied in score from 1-5.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study based in Thailand [14] demonstrated emergency medicine residents should provide POCUS knowledge in terms of POCUS used in emergency patients. To achieve competence in POCUS, emergency medicine residents must know how to use ultrasonography to detect both normal and abnormal anatomy and physiology, especially in situations most similar to actual patients' clinical context.…”
Section: Introductionmentioning
confidence: 99%
“…27 Training courses in POCUS were limited in the medical training center, especially for emergency medicine residents. 28 This initial effort to apply POCUS in prehospital care needs to be reproduced in the community to improve the current situation. The trained emergency medicine physicians could be potential trainers in future training programs for the other levels of EMS providers.…”
Section: Discussionmentioning
confidence: 99%
“…The value of P was determined based on data extracted from a previously published study. 13 To ensure statistical significance, a minimum sample size of eight was deemed appropriate for this particular investigation.…”
Section: Methodsmentioning
confidence: 99%